Combustion of bituminous coal loaded with copper salts; Fuel; Vol. 286 - Larionov K. B. Kirill Borisovich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Mishakov I. V. Iljya Vladimirovich; Tsibulskii (Tsibulskiy) S. A. Svyatoslav Anatolievich; Tabakaev R. B. Roman Borisovich; Vedyagin A. A. Aleksey Anatolievich; Gromov A. A. Aleksandr Aleksandrovich (2021, 2021)
Title screen